2002
DOI: 10.1002/gps.540
|View full text |Cite
|
Sign up to set email alerts
|

The clinical phenotype of familial and sporadic late onset Alzheimer's disease

Abstract: Apart from an earlier age of onset, patients with familial LOAD, as a group, do not have major differences in their clinical phenotype compared to patients with sporadic LOAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Familial cases of the disease appear to have the same clinical and pathologic phenotypes as sporadic cases. Notably, a study designed to investigate the existence of specific differences in the clinical features of fAD and sAD revealed that—apart from the age of onset, where a positive family history of dementia was associated with an earlier beginning—no major differences in terms of clinical phenotype—including rate of cognitive decline, duration of illness, and presence of non-cognitive symptoms—were reported between fAD patients compared to patients with sporadic disease [38,39]. In another study, AD patients were examined to test the hypothesis that cases with a familial aggregation differ from cases without such an aggregation with reference to cognitive impairment.…”
Section: Issue 1—the Definition Of the Preclinical Stage Of Admentioning
confidence: 99%
“…Familial cases of the disease appear to have the same clinical and pathologic phenotypes as sporadic cases. Notably, a study designed to investigate the existence of specific differences in the clinical features of fAD and sAD revealed that—apart from the age of onset, where a positive family history of dementia was associated with an earlier beginning—no major differences in terms of clinical phenotype—including rate of cognitive decline, duration of illness, and presence of non-cognitive symptoms—were reported between fAD patients compared to patients with sporadic disease [38,39]. In another study, AD patients were examined to test the hypothesis that cases with a familial aggregation differ from cases without such an aggregation with reference to cognitive impairment.…”
Section: Issue 1—the Definition Of the Preclinical Stage Of Admentioning
confidence: 99%
“…But, what if they fail? The effects of FAD mutations are unequivocally to bring forward the age of disease onset: yet, there are little data to support the case that they accelerate the progression of the disease once initiated (Holmes and Lovestone ; Godbolt et al . ; Snider et al .…”
Section: The Future: Are We Poised For Success or Failure?mentioning
confidence: 99%
“…But, what if they fail? The effects of FAD mutations are unequivocally to bring forward the age of disease onset: yet, there are little data to support the case that they accelerate the progression of the disease once initiated (Holmes and Lovestone 2002;Godbolt et al 2004;Snider et al 2005;Kumar-Singh et al 2006;Acosta-Baena et al 2011;Karran et al 2011). As FAD mutations likely all increase the probability of amyloid deposition, it could be the case that amyloid deposition triggers, but does not drive, the disease process.…”
Section: What Is the Connection Between Amyloid And Tau Pathologies?mentioning
confidence: 99%
“…Mutations in three genes (APP, PSEN1 and PSEN2) are known to cause familial early-onset AD [7][8][9]. Although there is no evidence that autosomal dominant inheritance of mutated genes causes late-onset AD, genetics does appear to play a role in the development of this more common form.…”
Section: Introduction To Alzheimer's Disease (Ad)mentioning
confidence: 97%